Emperical analysis of inflation dynamics evidence from Ghana and South Africa - Boateng, Alexander (My University, 2017)
Refer to docutment
Thesis (Ph.D. (Statistics)) -- University of Limpopo, 2017
Keywords: Inflation; Ghana; Inflation (Finance) -- Developing countries